A coalitional game‐based integrated framework for optimal power allocation in multirelay cooperative environment. (7th September 2017) - Lamba, Amanjot Kaur; Kumar, Ravi; Sharma, Sanjay
Summary: Cooperative relaying has emerged as an efficient transmit strategy in wireless networks affected by fading. In multirelay scenarios, the performance of cooperative systems is heavily influenced by resource allocation among the available relays. However, in practical scenarios, a relay may not help unless the cooperation improves its own utility. To address the above problem, this paper introduces a novel integrated game‐theoretic framework that involves incentive‐based optimal power allocation among the cooperating relays. Coalition formation game has been used to model the cooperation among relays that is integrated into a Stackelberg game, for considering the benefits of source and relays jointly. The game theoretic framework has been implemented with an objective to find an optimal and stable coalition set of relays that not only maximizes their utilities but also helps the source to allocate the optimal power to the relays at the optimal price, thereby increasing its utility too. Simulation results have confirmed that the proposed game theoretic solutions achieve comparable performance in system throughput as compared with the centralized approach. Abstract : This paper proposes a novel game‐theoretic framework for optimal power allocation. The proposed scheme involves incentive‐based power allocation under a coalition formation game that has been used to model the cooperation among relays. The proposed framework achieves (i) an optimal and stable coalition set of relays, (ii) an optimal set of relays with maximum utilities, (iii) allocation of optimal power to the relays by the source at an optimal price, and (iv) performance comparable to that of the centralized scheme even in the absence of complete channel state information.